Vitamin A Concentration in Cord and Maternal Serum and its Relation to Birth Weight - Barua, Dipi; Chowdhury, TA; Barua, Ashim Ranjan (Ibrahim Medical College Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Low birth weight (LBW) is a common problem in Bangladesh associated with poor survival, growth and development. Among many factors, Vitamin A deficiency is thought to be associated with LBW. To investigate this relation a study was conducted at Maternity and Child Health Training Institute at Azimpur, Dhaka during January 2000 - July 2002. One hundred pregnant women (38-40 wks of gestation) with their newborns were included. Weights of the newborns were recorded within 20 - 30 minutes of delivery. Vitamin A level was estimated in maternal and cord serum. The newborns having weight <2500gm showed Vitamin A level of 49.40 ± 3.04μg/dl in their maternal serum while those weighing ≥2500gm had a Vitamin A level of 60.18 ± 2.03μg/dl in their maternal serum. A trend of increased maternal serum Vitamin A level was observed with increasing birth weight. Thus neonates with higher birth weights were found to be associated with higher values of maternal serum Vitamin A, though not being statistically significant. Ibrahim Med. Coll. J. 2009; 3(1): 9-12 Key words: LBW, Vitamin A, cord blood, neonates doi: 10.3329/imcj.v3i1.2911